2013
DOI: 10.1523/jneurosci.4522-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Functional Specializations of the Ventral Intraparietal Area for Multisensory Heading Discrimination

Abstract: The ventral intraparietal area (VIP) of the macaque brain is a multimodal cortical region with directionally-selective responses to visual and vestibular stimuli. To explore how these signals contribute to self-motion perception, neural activity in VIP was monitored while macaques performed a fine heading discrimination task based on vestibular, visual, or multisensory cues. For neurons with congruent visual and vestibular heading tuning, discrimination thresholds improved during multisensory stimulation, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
166
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(194 citation statements)
references
References 61 publications
27
166
0
1
Order By: Relevance
“…Consistent with previous reports (10,15,28), r noise was positively correlated with r signal in both intact and lesioned animals (ANCOVA; intact, P < 0.001; lesioned, P = 0.03; Fig. 5C).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous reports (10,15,28), r noise was positively correlated with r signal in both intact and lesioned animals (ANCOVA; intact, P < 0.001; lesioned, P = 0.03; Fig. 5C).…”
Section: Resultssupporting
confidence: 92%
“…Traditional tools for assessing functional links between single neurons and perceptual decisions include quantification of trial-by-trial correlations between neuronal activity and perceptual reports for ambiguous stimuli (1). Such "choice probabilities" (CPs) have been reported in visual (2-9), parietal (10), and somatosensory (11) cortical areas. Computational studies have also shown that the extent of correlated noise in a pool of neurons profoundly affects CPs (12)(13)(14).…”
mentioning
confidence: 99%
“…We recorded from area VIP, because VIP neurons exhibit heading tuning based on optic flow (20)(21)(22)(23)(24) that is tolerant to real or visually simulated eye rotations (11,12), and also because VIP neurons respond to smooth pursuit eye movements (25). In addition, previous studies have reported gain fields-changes in the amplitude of heading tuning curves caused by rotations (11,12).…”
mentioning
confidence: 99%
“…Hence, the quest to untangle and exploit the normative rules and principles of multisensory processing will be vital for understanding decision-making in the intersection of sensation, action, and experience. Gu et al 2008) and (B) VIP (from Chen et al 2013a). Data are shown as scatter plots of the ratio of the threshold measured in the combined condition relative to the prediction for optimal cue integration (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…0˚heading denotes straight forward translation, whereas positive/negative numbers indicate rightward/leftward directions, respectively. Data (from Gu et al 2008 andChen et al 2013a) illustrate firing rate means and SE. The numbers on each panel illustrate the "Congruency Index" for each cell.…”
Section: Neural Correlates Of Multisensory Heading Perceptionmentioning
confidence: 99%